Aspek Mitologi dalam Novel Gadis Kretek Ditinjau dari Teori Strukturalisme Lèvi-Strauss - Alfiyyah Sausan Mashuri; Arina Alhaq; Arinda Safira; Aulia Nikmatul Fauziah; Dini Afriyanti; Ikfina Izzatul Malikhah; Suryo Ediyono (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2024)
This study aims to analyze the mythological (mytheme) aspects of Javanese culture contained in the novel